Sound-Symbolic Semantics of Written Japanese Vowels in a Paper-Based Survey Study - Ando, Misa; Liu, Xinyi; Yan, Yan; Yang, Yutao; Namba, Shushi; Abe, Kazuaki; Kambara, Toshimune (Frontiers in Communication, 2021)
Verbal sounds can be associated with specific meanings, a phenomenon called sound symbolism. Previous findings of sound symbolism have shown that words including specific consonants or vowels or mouth shapes to pronounce specific vowels associate with specific and subjective physical and emotional evaluations. The purpose of this study was to examine whether each written vowel in a given language was individually associated with specific subjective evaluations. Six hundred and thirteen participants used 5-point semantic differential scales for 10 features (size, closeness, thickness, width, weight, height, depth, affection, excitement and familiarity) to rate written Japanese vowels (a, i, u, e and o). The results showed that the size, closeness, thickness and width of a, u and o were significantly higher than those of i and e, whereas the affection and familiarity of a were higher than the others. These results were consistent with previous findings in which vowels in sound-symbolic words have been associated with physical (i.e. size, closeness, thickness and width) and emotional (i.e. affection) evaluations. Our findings suggest that each written Japanese vowel itself, with its individual characteristics, could individually contribute to specific and subjective physical and emotional evaluations. These findings provide insights on how we could better use letters for communicative relationships among writers and readers.